Preparation method and application of loofah sponge cellulose fiber aerogel

By using loofah cellulose fiber to prepare aerogel, the problems of complex and high cost of preparation of existing aerogel materials are solved, and the oil treatment effect with efficient adsorption and good mechanical properties is achieved, which is suitable for the adsorption and recovery of oil. .

CN119431872APending Publication Date: 2025-02-14DALIAN POLYTECHNIC UNIVERSITY
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411460684.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the treatment of oil contamination, existing aerogel materials have problems such as high preparation cost, complex process, easy to produce toxic by-products and difficult to produce on a large scale. Biomass aerogels have complex preparation process, low adsorption ratio, and mechanics. Poor performance and other defects.

Method used

Using loofah cellulose fibers as raw materials, a suspension with a large number of micro-nano-scale fibers on the fiber surface is prepared by pulverizing, chemical and mechanical grinding treatment, and aerogels are prepared by hydrophobic modification of silane coupling agent and vacuum freeze-drying method. .

Benefits of technology

The prepared loofah cellulose fiber aerogel has high adsorption performance, good mechanical properties and low preparation cost. It can efficiently adsorb a variety of oils and organic solvents, and can be recycled multiple times. It is suitable for the adsorption of oils and Recycle.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005091787460000011
    Figure HDA0005091787460000011
  • Figure HDA0005091787460000012
    Figure HDA0005091787460000012
  • Figure HDA0005091787460000013
    Figure HDA0005091787460000013
Patent Text Reader

Abstract

The invention discloses a preparation method and application of loofah sponge cellulose fiber aerogel, and belongs to the technical field of aerogel materials. The preparation method comprises the following steps: preparing loofah sponge cellulose fiber with a large number of cellulose microfibrils on the surface layer by taking a natural biomass material loofah sponge fiber as a raw material, and preparing the loofah sponge cellulose fiber aerogel through silane coupling agent hydrophobic modification and vacuum freeze drying. According to the preparation method, the cost can be remarkably reduced, the production process is simplified, the aerogel has high porosity and good self-cleaning performance, various organic solvents and oil pollutants in sewage can be efficiently adsorbed, the adsorption capacity is high, the speed is high, and the adsorbed oil liquid can be kept for a long time without secondary leakage. Meanwhile, the material has good mechanical properties, can be repeatedly used, is easy to degrade after being used, and has wide application prospects in the aspects of environmental governance and biomass resource waste utilization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a preparation method of a loofah cellulose fiber aerogel and application thereof, belonging to the technical field of aerogel materials. Background Art

[0002] Adsorption has become the main method for treating oil pollution. Recently, various aerogel materials, such as silicon-based aerogel and carbon-based aerogel, have shown great potential in the field of oil pollution removal and have been extensively developed and studied. However, such materials still have many disadvantages, such as high preparation cost, complex process, easy generation of toxic byproducts during the preparation process, and difficulty in industrial production, which greatly hinders their practical application. Biomass aerogel is a new type of green adsorption material with a three-dimensional porous structure, low density, high specific surface area, good biocompatibility and biodegradability. However, at present, biomass aerogel has defects such as complex preparation process, low adsorption rate, poor mechanical properties and difficulty in large-scale production. Therefore, the research and development of adsorption materials with simple preparation process, high adsorption capacity and good mechanical properties has received extensive attention from scientific researchers.

[0003] Luffa fiber is the vascular bundle of the dried mature fruit of the Cucurbitaceae plant luffa, mainly composed of cellulose, hemicellulose, lignin and wax, with a unique three-dimensional network structure and hydrophobic and lipophilic properties. It is a natural oil adsorption material with abundant sources, low prices, environmental friendliness and biodegradability. It is easy to collect and process after use, and has been widely used in the field of oil adsorption. However, luffa adsorption materials still have defects such as low adsorption rate and poor reusability, and their performance still needs to be improved. Summary of the invention

[0004] The technical problem solved by the present invention is: how to use natural biomass materials to prepare an oil absorption and recovery material with low cost, good adsorption performance and mechanical properties, and can be recycled multiple times. The present invention uses loofah fibers with a natural three-dimensional network structure as raw materials to prepare aerogel materials, which simplifies the process flow and reduces the preparation cost while improving the mechanical and adsorption properties of the material. The aerogel of the present invention can efficiently absorb a variety of organic solvents and oil pollutants in sewage, has high adsorption capacity and fast rate, and can maintain the adsorbed oil for a long time without secondary leakage.

[0005] In order to solve the above technical problems, the present invention provides a method for preparing loofah cellulose fiber aerogel, which comprises subjecting pulverized loofah short fibers to chemical and mechanical grinding treatment to prepare a loofah cellulose fiber suspension having a large number of micro-nano-scale fibrils on the fiber surface, and then subjecting the suspension to hydrophobic modification with a silane coupling agent and vacuum freeze-drying treatment to obtain the aerogel.

[0006] Specifically, the present invention also provides a specific preparation method of the above-mentioned loofah cellulose fiber aerogel, comprising the following steps:

[0007] Step 1: Preparation of loofah cellulose fiber: alkaline treatment is performed on the loofah fiber to remove wax, lignin and hemicellulose on the fiber surface to expose the cellulose inside the fiber, and then the fiber is washed with deionized water; the treated loofah fiber is then subjected to mechanical grinding to obtain loofah cellulose fiber with a large amount of cellulose microfibrils on the surface;

[0008] Step 2: hydrophobic modification of luffa cellulose fiber: adding deionized water to the luffa cellulose fiber obtained in step 1 and stirring at room temperature for 1-2 hours to prepare a luffa cellulose fiber suspension of desired concentration; adjusting the pH value of the luffa cellulose fiber suspension to acidic, adding a silane coupling agent thereto, and stirring the reaction at room temperature to obtain a modified luffa cellulose fiber suspension;

[0009] Step 3: Aerogel preparation: The modified luffa cellulose fiber suspension obtained in step 2 is placed in a mold for freeze molding, and then freeze-dried to obtain luffa aerogel.

[0010] Preferably, the loofah fibers in step 1 are mechanically crushed loofah fibers.

[0011] Preferably, the length of the loofah fibers in step 1 is about 100-2100 μm.

[0012] Preferably, the alkali treatment in step 1 is specifically as follows: placing the loofah fiber in a NaOH solution, using a water bath heating pot to treat at 80-150° C. for 1-3 hours, and using deionized water to rinse the fiber until it is neutral; the concentration of the NaOH solution is 1-15wt%.

[0013] Preferably, the conditions of the mechanical grinding treatment in step 1 are: beating degree 20-70°SR, temperature 25-60°C, and time 0.5-3h.

[0014] Preferably, the content of loofah cellulose fibers in the loofah cellulose fiber suspension obtained in step 2 is 0.1-8.0 wt %.

[0015] Preferably, the silane coupling agent in step 2 is vinyltrimethoxysilane or methyltrimethoxysilane, etc.; the pH value is adjusted to 3-5 using hydrochloric acid or acetic acid.

[0016] Preferably, the concentration of the silane coupling agent in step 2 is 1-10 wt %.

[0017] Preferably, the stirring reaction conditions in step 2 are: stirring speed 800-2000 rpm, time 4-6 hours.

[0018] Preferably, the specific conditions for freeze molding in step 3 are: freezing in a refrigerator at -20 to -25°C for 8 to 20 hours.

[0019] Preferably, the vacuum freeze-drying conditions in step 3 are: temperature -60 to -70°C, time 24 to 72 hours.

[0020] The present invention also provides a loofah cellulose fiber aerogel prepared by the above preparation method; the density of the aerogel is 2.0-20 mg / cm 3 The oil absorption rate is 90-200g / g and the contact angle is 130-170°.

[0021] The present invention also provides the use of the loofah cellulose fiber aerogel in oily wastewater treatment, oil-water separation and oil recovery.

[0022] Preferably, the application includes selectively adsorbing one or more of white oil, soybean oil, pump oil, gasoline, vegetable oil and organic solvents.

[0023] More preferably, the organic solvent includes any one or more of ethanol, isopropanol, N,N-dimethylformamide, dimethyl sulfoxide, chloroform, toluene and acetone.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The present invention proposes a method for preparing a loofah cellulose fiber aerogel using a biodegradable and environmentally friendly natural biomass material loofah. The method prepares a loofah cellulose fiber having a large number of cellulose microfibrils on the surface by crushing, chemically and mechanically treating the loofah, and prepares the aerogel material by superhydrophobic modification and vacuum freeze drying. Compared with the traditional cellulose extraction method for preparing aerogel, the present invention simplifies the preparation process and reduces the preparation cost, and is easy to scale production.

[0026] 2. The loofah cellulose fiber aerogel prepared by the present invention has a stable three-dimensional porous structure, high porosity (up to 99.4%), high adsorption performance, good self-cleaning performance and mechanical properties. The aerogel density is about 2.0-20 mg / cm 3, the contact angle can reach 130-170°. It can effectively adsorb a variety of oils and organic solvents, such as soybean oil, vacuum pump oil, chloroform, DMF and ethanol, and the adsorption rate can be as high as 90-200g / g at room temperature. At the same time, it has excellent oil retention performance (oil retention rate is as high as 97%), can quickly (within 10s) and efficiently separate and stably maintain the adsorbed oil, and has high application value in applications such as oil-water separation and oil pollution removal.

[0027] 3. The loofah aerogel prepared by the present invention has excellent mechanical properties and can be reused for oil adsorption and recovery. The used material can also be treated by natural biodegradation, is easy to degrade, has high environmental friendliness, and has broad application prospects in environmental governance and biomass resource waste utilization. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The aerogel prepared in Example 1 selectively adsorbs chloroform in a mixture of water and chloroform; wherein, (a) shows the aerogel extending into water; (b) shows the aerogel selectively adsorbing soybean oil but not water in a mixture of water and soybean oil; and (c) shows the aerogel being taken out after completely adsorbing the soybean oil in water.

[0029] Figure 2 The aerogel prepared in Example 1 was repeatedly bent and twisted without changing its shape; (a) was an aerogel that could be cut into a circle and could still return to its original shape after being folded; (b) was an aerogel that was cut into a long strip and could still return to its original shape after being twisted.

[0030] Figure 3 The self-cleaning property of the aerogel prepared in Example 2, wherein (a) milk tea is dropped on the surface of the aerogel, and (b) the milk tea flows down the surface of the aerogel without contaminating or dirtying the surface.

[0031] Figure 4 Schematic diagram of the surface oil floating interception device used in Example 2. DETAILED DESCRIPTION

[0032] In order to make the present invention more clearly understood, preferred embodiments are described in detail as follows.

[0033] All raw materials used in the following examples are commercially available products.

[0034] Example 1

[0035] This embodiment provides a method for preparing a loofah cellulose fiber aerogel material, wherein the fibers are crushed into powder, and then subjected to chemical and mechanical treatment to obtain a loofah cellulose fiber suspension, the pH of the solution is adjusted to acidic, a silane coupling agent is added for hydrophobic modification, and the mixture is poured into a mold and frozen and then placed in a freeze-drying method to prepare a loofah cellulose fiber aerogel. The specific steps are as follows:

[0036] Step 1: Preparation of loofah cellulose fibers:

[0037] The loofah fibers with a length of about 400-1500 μm after crushing are placed in a 7wt% NaOH solution, treated in a water bath at 120°C for 2h to remove the wax on the surface of the loofah fibers, and rinsed with deionized water until neutral; then the loofah fibers are mechanically treated with a beater (beating degree 70°SR, temperature 25±5°C, time 1h) to obtain loofah cellulose fibers;

[0038] Step 2: Hydrophobic modification of loofah cellulose fibers:

[0039] The loofah cellulose fiber obtained in step 1 was added with deionized water and stirred at room temperature for 1 h to prepare a suspension with a fiber content of 2 wt%, the pH of the suspension was adjusted to between 3 and 4 using hydrochloric acid, 4 wt % of methyltrimethoxysilane was added dropwise to the suspension using a pipette, and stirred at room temperature using a magnetic stirrer for 6 h at a speed of 1500 rpm;

[0040] Step 3: Preparation of aerogel:

[0041] The modified suspension obtained in step 2 is placed in a mold and frozen in a refrigerator at -25°C for 10 hours; and then freeze-dried in a freeze dryer at -60°C for 72 hours to obtain loofah cellulose fiber aerogel.

[0042] The loofah aerogel (size 2 cm×2 cm×1.2 cm) prepared in this example has a density of 2.0 mg / cm 3 , with a contact angle of 170°, was placed in a mixture of water and soybean oil (volume ratio of soybean oil to water 1:40), and the aerogel could quickly (within about 10 seconds) and selectively adsorb the soybean oil solution from the mixed solution (see Figure 1 ), the adsorption rate is as high as 126g / g, and the oil retention rate can reach 97% (after the aerogel adsorbed to oil saturation was placed on an iron net for 48 hours, it was found that the oil inside did not leak significantly). At the same time, the aerogel's adsorption rate for chloroform solution is as high as 200g / g, showing excellent adsorption capacity.

[0043] The loofah aerogel prepared in this example can be cut into a circle (radius of about 5 cm) or a long strip (size of 10 cm×2 cm×1 cm) for testing. The aerogel has excellent mechanical properties and can be twisted and rotated without changing the shape or collapsing the structure. Figure 2 shown.

[0044] The loofah aerogel (size 4cm×4cm×4cm) prepared in this example was placed in a mixed solution of water and mineral oil (volume ratio of water to mineral oil 8:1). The oil inside the aerogel can be directly squeezed out by external force for recovery and reuse. The recovery efficiency of mineral oil can reach 75%, showing good reuse performance.

[0045] Example 2

[0046] This embodiment provides a method for preparing a loofah cellulose fiber aerogel material, wherein the fibers are crushed into powder, and then subjected to chemical and mechanical treatment to obtain a loofah cellulose fiber suspension, the pH of the solution is adjusted to acidic, a silane coupling agent is added for hydrophobic modification, and the mixture is poured into a mold and frozen and then placed in a freeze-drying method to prepare a loofah cellulose fiber aerogel. The specific steps are as follows:

[0047] Step 1: Preparation of loofah cellulose fibers:

[0048] The loofah fibers with a length of about 300-1000 μm after crushing are placed in a 10wt% NaOH solution, treated in a water bath at 90°C for 1.5h to remove the wax on the surface of the loofah fibers, and rinsed with deionized water until neutral; then the loofah fibers are mechanically treated with a beater (beating degree 40°SR, temperature 25±5°C, time 2h) to obtain loofah cellulose fibers;

[0049] Step 2: Hydrophobic modification of loofah cellulose fibers:

[0050] The loofah cellulose fiber pulp prepared in step 1 was added with deionized water and stirred at room temperature for 1 hour to prepare a suspension with a fiber content of 3 wt%, the pH of the suspension was adjusted to between 3 and 4 using hydrochloric acid, 6 wt % of methyltrimethoxysilane was added dropwise to the suspension using a pipette, and stirred at room temperature for 8 hours using a magnetic stirrer at a speed of 1200 rpm;

[0051] Step 3: Preparation of aerogel:

[0052] The modified suspension obtained in step 2 is placed in a mold and frozen in a refrigerator at -20°C for 10 hours; then a freeze dryer is used to freeze-dry for 72 hours at -60°C to obtain the loofah cellulose fiber aerogel.

[0053] The aerogel (petal-shaped, about 5 cm in diameter) prepared in this example has excellent hydrophobic properties, with a contact angle of up to 150°. When 5 ml of milk tea is dropped on its surface, the milk tea will flow along the surface of the aerogel without penetrating into the interior of the aerogel to contaminate or stain the surface (see Figure 3 ), showing excellent self-cleaning properties.

[0054] The loofah cellulose fiber aerogel (size 10 cm×10 cm×4 cm) prepared in this example has a density of 14.5 mg / cm 3 , which is used to intercept the filter material and place it in the flowing water / oil mixture. The schematic diagram of the test device is shown in Figure 4 As shown. The aerogel was inserted into the middle of the water tank, and a mixed solution of mineral oil and water (volume ratio of mineral oil to water was 1:10) was injected into the water tank from the left. It was found that the oil could be successfully intercepted by the aerogel on the left side of the water tank, leaving clear water on the right side of the water tank. The loofah cellulose fiber aerogel showed excellent interception and filtration performance for oil.

Claims

1. A method for preparing a loofah cellulose fiber aerogel, characterized in that: The following steps are involved: Step 1: Preparation of loofah cellulose fiber: treating the loofah fiber with alkali, and then washing it with deionized water; then mechanically grinding the treated loofah fiber to obtain loofah cellulose fiber; Step 2: hydrophobic modification of luffa cellulose fiber: adding deionized water to the luffa cellulose fiber obtained in step 1, stirring at room temperature for 1-2 hours, and preparing a luffa cellulose fiber suspension; adjusting the pH value of the luffa cellulose fiber suspension to acidic, adding a silane coupling agent thereto, stirring and reacting at room temperature, and obtaining a modified luffa cellulose fiber suspension; Step 3: Aerogel preparation: The modified luffa cellulose fiber suspension obtained in step 2 is freeze-formed, and then freeze-dried to obtain luffa aerogel.

2. The preparation method according to claim 1, characterized in that: The loofah fibers in step 1 are mechanically crushed loofah fibers, and the length of the loofah fibers is 100-2100 μm.

3. The preparation method according to claim 1, characterized in that: The conditions of the mechanical grinding treatment are: beating degree 20-70°SR, temperature 25-60°C, and time 0.5-3h.

4. The preparation method according to claim 1, characterized in that: The alkali treatment in step 1 is specifically as follows: placing the loofah fiber in a NaOH solution, using a water bath heating pot to treat at 80-150° C. for 1-3 hours, and using deionized water to rinse the fiber until it is neutral; the concentration of the NaOH solution is 1-15wt%.

5. The preparation method according to claim 1, characterized in that: The content of the loofah cellulose fibers in the loofah cellulose fiber suspension obtained in step 2 is 0.1-8.0 wt %.

6. The preparation method according to claim 1, characterized in that: The pH value in step 2 is adjusted to 3-5 using hydrochloric acid or acetic acid; the stirring reaction conditions are: stirring speed 800-2000 rpm, time 4-6 hours.

7. The preparation method according to claim 1, characterized in that: The silane coupling agent in step 2 is vinyl trimethoxy silane or methyl trimethoxy silane, and the concentration of the silane coupling agent is 1 to 10 wt %.

8. The preparation method according to claim 1, characterized in that: The freezing molding conditions in step 3 are: freezing in a refrigerator at -20 to -25°C for 8-20 hours; the vacuum freeze drying conditions are: temperature -60 to -70°C, time 24 to 72 hours.

9. Luffa cellulose fiber aerogel prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the loofah cellulose fiber aerogel according to claim 9 in oily wastewater treatment, oil-water separation and oil recovery.

Citation Information

Cited By

  • Aerogel for treating emulsified oily wastewater and preparation method thereof

    CN120532465A

  • Hydrophobic cellulose aerogel and preparation method thereof

    CN120988345A